First record of Dryocosmus kuriphilus in Greece. (19th July 2016) - Michaelakis, A.; Papachristos, D.; Chytas, D. A.; Antonopoulou, P. D.; Milonas, P. G.; Avtzis, D. N.
Abstract : After the first introduction of chestnut gall wasp, Dryocosmus kuriphilus, in Italy, it has spread rapidly in several other European countries, probably largely due to trade in chestnut plants. Despite the measures taken to prevent further spread of this pest to other countries, D. kuriphilus was detected in Greece for the first time in 2014. However, surveys have shown that the pest is still of very limited distribution in Greece. Having faced the damage caused by chestnut blight ( Cryphonectria parasitica ) over the last 50 years, the production of chestnuts in Greece is now seriously threatened by chestnut gall wasp, which has already caused extensive losses in chestnut production of other countries. In order to minimize the impact of chestnut gall wasp, control measures are being designed involving the release of the parasitoid Torymus sinensis .